Wczesnego chrześcijaństwa kłopoty z ciałem – rozwiązania Klemensa Aleksandryjskiego - Łucarz, Stanisław (Horyzonty Wychowania, 2017)
This article is aimed to demonstrate the difﬁ culties concerning the question of human body that the early Christianity faced. It is also intended to present one of the ﬁ rst attempts to solve those problems. That difﬁ culties are bond closely with the fact that in the early Christianity ﬂ owed together two rich streams of thoughts and traditions: the ancient Greek and the biblical one. The Greek view of the body was very negative. For Plato the body was the prison and the tomb of the soul and the aim of both men and philosophy was to free the soul from this oppression. On the contrary, the biblical view is positive and the body is presented as the essential component of the human nature, with its most sacred destiny-the resurrection. The platonic negativism is linked with a permissive ethic of the body, while its biblical appreciation is connected with a very demanding one. Still before the origin of Christianity, the platonic negativism and the biblical demanding ethic had already met together in the philosophy of Philo of Alexandria. The early Christianity in herited this unlucky combination. One of the ﬁ rst Christian philosophers who tried to solve this dilemma was Clement of Alexandria. He attempted to reestablish the dignity of the body and thus base the Christian ethic on this positive ground.